2013
DOI: 10.1016/j.exger.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells from the elderly display an intrinsic defect in the production of IL-10 in response to Lithium Chloride

Abstract: Chronic, low grade inflammation is a characteristic of old age. Innate immune system cells such as dendritic cells (DCs) from the elderly display a pro-inflammatory phenotype associated with increased reactivity to self. Lithium is a well-established anti-inflammatory agent used in the treatment of bipolar disorders. It has also been reported to reduce inflammation in DCs. Here, we investigated whether Lithium is effective in reducing the inflammatory responses in DCs from the elderly. The effect of Lithium Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Furthermore, in some studies lithium was found to lack a significant influence on IL-6 production. 67,85,86 Taken together, these data suggest that the effect of lithium on IL-6 varies under different experimental conditions.…”
Section: −62mentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, in some studies lithium was found to lack a significant influence on IL-6 production. 67,85,86 Taken together, these data suggest that the effect of lithium on IL-6 varies under different experimental conditions.…”
Section: −62mentioning
confidence: 76%
“…65,66,104 However, most of the reviewed studies found opposite results, demonstrating that lithium inhibits INF-γ synthesis. 82,86,87,[104][105][106]115,116 For example, lithium was found to decrease INF-γ levels in whole blood cultures from normal control subjects. 104 Tay et al 82 showed that lithium reduced INF-γ production in serum and multiple organs of bacteria-treated mice.…”
Section: −62mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some in vitro studies suggest a biphasic proinflammatory effect of lithium after short-time use (Kleinerman et al, 1989;Petersein et al, 2015) and an attenuating antiinflammatory effect after longer-term use (Boufidou et al, 2004;Knijff et al, 2007;Maes et al, 1999;Rapaport and Manji, 2001). While some of these in vitro findings have been countered, the immunoregulatory properties of lithium are still mainly accepted (Agrawal et al, 2013;Himmerich et al, 2013Himmerich et al, , 2014. Lithium has been proposed to exert its immunomodulatory role at the gene expression level.…”
Section: Discussionmentioning
confidence: 94%
“…As such, TLR2 could serve as a target for therapeutic treatment of allergic asthma [13][14][15]. Moreover, the TLR2 agonist Pam 3 CSK 4 exhibits unique immunomodulatory properties, characterized by the capacity to induce robust cytokine production by naive CD4+ T lymphocytes (both IL-10 and IFN-γ) [16][17][18][19]. In a murine asthma model, Pam 3 CSK 4 treatment improved allergic hyper-responsiveness within the airways (AHR).…”
mentioning
confidence: 99%